Poesía y autobiografía en un momento de la obra de Alfonso Reyes (1908-1916) - Stanton, Anthony (El Colegio de México, 2013)
The article explores the reactions by Reyes in letters, prose texts andpoems to the questions posed by his life before and after the traumaticdeath of his father in 1913. Perceived as a numinous figure thatembodies “the civic religion”, the father is sacralized as a “militaryChrist”. Unable to follow his route, the son achieves the (re)conciliationof his country on an imaginary plane, in texts that propose theharmonic coexistence of what is heterogeneous in a cultural miscegenationof impurity. The author hides and reveals himself in dramaticmasks: the faithful subject, the son-apostle, the traveller, the domesticslave, the dispossessed one, the prodigal son, the outcast, the philologist.The poems analysed are read as fragments of a fictitious autobiography.